Numerical and measurement investigation of the thermal bridge caused by the pipe passing through the insulated wall (2019)
The local thermal bridges cause problems on buildings. The aim of the analysis presented in the paper is to study the passage of pipes through a well-insulated exterior wall. Two possible pipe location in thermal insulation have been investigated: just below the exterior surface and fully embedded in the insulation. Numerical 3D calculations using the finite element method showed possible critical areas in this detail with increased relative humidity. Due to the limitations of numerical calculations, similar measurements on a sample with real dimensions were made in climatic chambers. By taking a detailed reading of the temperature and the relative humidity around the pipe in the wall, the results of the numerical calculations have thus been refined.